Negotiating trade liberalization at the WTO domestic politics and bargaining dynamics - Conceição, Eugénia da 1970- (Palgrave Macmillan, 2011)
This book shows how domestic political institutions and the lack of time pressure have an impact on negotiations at the WTO. It provides detailed information on WTO ministerial meetings as well as on the political economy of trade policy in the EU, U.S., Brazil, and Australia
Literaturverz. S. 238 - 262
Keywords: World Trade Organization; International trade; Political economy; International relations; Development studies; Economics; Globalisierung; Internationale Politik; Wirtschaft; POLITICAL SCIENCE / Globalization; Commercial policy; POLITICAL SCIENCE / International Relations / Diplomacy; Free trade; POLITICAL SCIENCE / NGOs (Non-Governmental Organizations); Handelspolitik; Freier Warenverkehr